Perancangan Media Pembelajaran Informatika Menggunakan Thunkable - Defrian, Fauzi Risna; Okra, Riri; Derta, Sarwo; Musril, Hari Antoni; Yuspita, Yulifda Elin (Intellect : Indonesian Journal of Learning and Technological Innovation, 2023)
This article aims to produce an informatics learning media at SMPN 2 Ampek Angkek, this problem stems from the fact that in the learning process teachers in explaining teaching material still use manual/non-computerized media such as using books and blackboards, this has an impact on the learning atmosphere of students feeling bored and not focused on studying. Therefore, computerized learning media is needed that can be used during the learning process. This research model is research and development (Research and Development) with the development model framework used being 4 D. This research produces learning media applications that can be used by teachers and students in application-based growth and development experiences via Android. The validation test carried out by 4 experts got a final score of 0.8 with valid results, the results of the practicality test from 1 expert got a final score of 0.9 with a very high class and the results of the item effectiveness test from 15 students got a score of 0.8 with high feasibility classification. From the results of this research, the learning media that has been designed has been tested for its validity, practicality and effectiveness, and this learning media application can be used by teachers and students in the informatics learning process. Abstrak Artikel ini bertujuan untuk menghasilkan sebuah media pembelajaran informatika di SMPN 2 Ampek Angkek, persoalan ini berangkat bahwa dalam proses pembelajaran guru dalam menjelaskan materi ajar masih menggunakan media manual/non-komputerisasi seperti menggunakan buku dan papan tulis, ini berdampak pada suasana pembelajaran siswa merasa jenuh dan tidak fokus belajar. Oleh karena itu dibutuhkan media pembelajaran berbasis komputerisasi yang dapat digunakan selama proses pembelajaran. Model penelitian ini adalah penelitian dan pengembangan (Research and Development) dengan kerangka kerja model pengembangan yang digunakan adalah 4D. Penelitian ini menghasilkan aplikasi media pembelajaran yang dapat digunakan oleh guru dan siswa dalam pengalaman tumbuh kembang berbasis aplikasi melalui android. Uji Validasi yang dilakukan oleh 4 ahli mendapatkan skor terakhir 0,8 dengan hasil valid, hasil dari uji praktikalitas dari 1 ahli mendapatkan skor terakhir 0,9 dengan kelas sangat tinggi dan hasil dari uji efektivitas item dari 15 peserta didik mendapatkan skor 0,8 dengan klasifikasi kelayakan tinggi.Dari hasil penelitian tersebut media  pembelajaran yang telah dirancang tersebut teruji kevalidan, kepraktisan dan keefektivitannya, dan aplikasi media pembelajarna ini dapat digunakan oleh guru dan siswa dalam proses pembelajaran informatika.